A NEW EDITION OF VENANTIUS FORTUNATUS: THE ART OF TRANSLATION - Gillian Knight (Exemplaria Classica, 2018)
Michael Roberts (ed., trans.), Venantius Fortunatus: Poems, Dumbarton Oaks medieval library, 46, Cambridge, MA-London: Harvard University Press, 2017, xx+910 pp., $29.95, ISBN 978-0-674-97492-0.